ChemInform Abstract: Change of Magnetic and Electronic Features Through Subtle Substitution in Cubic, Non‐centrosymmetric Extended Rare‐Earth Metal Cluster Complexes TR3X3. Issue 49 (3rd December 2013) - Steinberg, Simon; Valldor, Martin; Meyer, Gerd
Abstract [IrCe3]I3 is synthesized by comproportionation reactions of stoichiometric ratios of CeI3, Ce, and Ir (sealed Ta container, 1050 °C, 7 d).